Peran Pemahaman Petani Dalam Sistem Ketahanan Pangan Lokal Berbasis Sagu : Analisis Structural Equation Modeling di Papua Barat Daya - Krisna Fransina Lermating; Kristina Ina Tuto Tukan; Franklin D. Paiki (Journal of Innovative and Creativity, 2026)
Local food security is a strategic issue in Southwest Papua, which faces challenges due to changing consumption patterns and increasing dependence on imported food. Sago, as the main local staple food, has considerable potential to support household food security; however, its role is strongly influenced by farmers’ level of understanding. This study aims to analyze the role of farmers’ understanding in the sago-based local food security system using a Structural Equation Modeling (SEM) approach. The research was conducted in South Sorong Regency involving 125 sago farmers from five villages, namely Klaogin, Wersar, Tapiri, Konda, and Manelek, with 25 respondents representing each village. Data were collected through structured questionnaires using a five-point Likert scale. The latent variables analyzed included farmers’ knowledge, attitudes toward sago, local consumption culture, sago utilization, and household food security. Data analysis was performed using SEM-PLS software. The results indicate that farmers’ understanding has a significant effect on sago utilization and an indirect impact on household food security. Sago utilization was found to mediate the relationship between farmers’ understanding and household food security. These findings suggest that strategies to strengthen sago-based local food security should prioritize improving farmers’ knowledge, fostering positive attitudes, and reinforcing local consumption culture. This study provides policy implications for local governments in developing sustainable local food systems.